Engineering the Interaction Dynamics between Nano‐Topographical Immunocyte‐Templated Micromotors across Scales from Ions to Cells. Issue 49 (10th November 2020) - Wang, Jie; Ahmed, Rajib; Zeng, Yitian; Fu, Kaiyu; Soto, Fernando; Sinclair, Bob; Soh, Hyongsok Tom; Demirci, Utkan
Abstract: Manufacturing mobile artificial micromotors with structural design factors, such as morphology nanoroughness and surface chemistry, can improve the capture efficiency through enhancing contact interactions with their surrounding targets. Understanding the interplay of such parameters targeting high locomotion performance and high capture efficiency at the same time is of paramount importance, yet, has so far been overlooked. Here, an immunocyte‐templated nano‐topographical micromotor is engineered and their interactions with various targets across multiple scales, from ions to cells are investigated. The macrophage templated nanorough micromotor demonstrates significantly increased surface interactions and significantly improved and highly efficient removal of targets from complex aqueous solutions, including in plasma and diluted blood, when compared to smooth synthetic material templated micromotors with the same size and surface chemistry. These results suggest that the surface nanoroughness of the micromotors for the locomotion performance and interactions with the multiscale targets should be considered simultaneously, for they are highly interconnected in design considerations impacting applications across scales. Abstract : Magnetically responsive and nano rough micromotors using immunocyte as template demonstrate significantly increased surface interactions and significantly improved and highly efficient removal of various targets across multiple scales, from ions to cells, compared to smooth synthetic material templated micromotors with the same size and surface chemistry.